Modeling of active thermography through uncertainty quantification of parameters of the heat transfer equation - Tapia, Arturo Ortiz; Tsonchev, Rumen Ivanov; D´ıaz Viera, Mart´ın A.; Ortiz, Marlen Hern´andez (Annals of Mathematics and Physics, 2019)
Active thermography is an experimental technique used to analyze samples of materials or entire structures without destroying them, by means of a heat source, such as a laser beam of a given power. It is posed that such experimental procedure can be modeled mathematically through the complete equation of heat transfer. The uncertainty on the assumption of the value of the parameter emissivity of this equation is to be analyzed calculating the error between concrete experimental data and simulations where such parameter has been taken from the uniform distribution. To the extent of this research, specifically for active thermography, no previous attempt has been made for using at the same time the complete equation of heat transfer (without simplifications or linearizations), with the usage of uncertainty quantification for the specific experimental results to which the mathematical theory was applied.